The Effect of Employee Retention, Job Satisfaction, and Work Motivation on Employee Performance in PT. Citra Asri Buana - Debi Oktaviani; Sri Harini; Rachmat Gunawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Product quality, price, and promotion are all important variables in business growth. Good product quality, affordable pricing, and appealing promotions are all strategies that can be utilized to convince people to purchase. The study's goal is to investigate the simultaneous or partial influence of product quality, price, and marketing on the choice to buy shoes at a Shoe Store. Test the instrument using validity tests, reliability tests, classical assumption tests, and data analysis methods such as descriptive analysis, multiple linear regression analysis, multiple correlation analysis, coefficient of determination (R square), and hypothesis testing. According to the findings of the study, product quality, pricing, and promotion all have a favorable and significant effect on shoe choice in shoe stores.